Metabolome profiling of arbuscular mycorrhizal fungus treated Ocimum tenuiflorum L. provides insights into deviation in allocation of carbon compounds to secondary metabolism - Thokchom, Sarda Devi (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.